Basic Korean : learn to speak Korean in 19 easy lessons - Soohee Kim; Emily Curtis; Haewon Cho (North Clarendon, Vermont : Tuttle Publishing, 2019)
With an emphasis on practical daily communication, Basic Korean is a great introduction to those looking to learn the language whether on their own or with a teacher.
Keywords: Conversation and phrase books; Language and languages Study and teaching